Celiakija in laktozna intoleranca - Lunder, Mojca (Farmacevtski vestnik, 2016)
Celiac disease and lactose intolerance are closely related to wheat and milk, the two fundamental foods that entered human diet since the beginning of agriculture and animal husbandry ten thousand years ago. Celiac disease is chronic systemic autoimmune disorder that occurs among genetically predisposed subjects who are exposed to glutencontaining foods and other environmental factors. Correct diagnosis is essential for efficient and rational treatment and depends on non-avoidance of gluten containing foods beforehand. Despite novel treatment investigations and progress in understanding mechanisms of celiac disease, there is no pharmacotherapy in clinical practice yet. Lactose intolerance is a consequence of lactose malabsorption, due to reduced action of lactase. Primary lactose intolerance is a normal condition, present in 65 percent of adult population. To relieve gastrointestinal symptoms reduction of lactose intake is recommended. Complete restriction is unnecessary, since most lactose intolerant individuals can ingest small amounts of lactose. Lactose free milk products and supplements containing lactase are also available.
Keywords: brezglutenska dieta; Celiakija; gluten; laktazna persistenca; laktozna intoleranca; Patogeneza